PhD student' experiences of thesis supervision: 'management' as acceptance and strategy for action. - Krauss, Steven Eric; Ismail, Ismi Arif (Universiti Putra Malaysia Press, 2010)
Relationships with supervisors are regarded by graduate students the world over as the most important aspect affecting the quality of their overall university research experience. With the global increase in attrition rates of graduate students, much research is being conducted on understanding the nature of supervisory relationships in an attempt to develop ways of reducing attrition and improving PhD students’ and supervisors’ experiences of the PhD process. Despite this trend, from the perspective of graduate students, managing supervisory relationships is a topic that has received only scant coverage in the extensive literature on graduate supervision. In response to this gap, eighteen students from diverse backgrounds studying at one Malaysian university were interviewed using a combination of in-depth, one-on-one interviews, and focus group discussions. The results illuminated the central theme of ‘management’ of the supervisory relationship and included both management of self and supervisor. Managing the supervisory experience was further reduced to two streams: 1) acceptance of the situation, and 2) responding proactively to the situation so as to optimize the PhD research experience. The findings raise several issues related to the role of managing one’s experience in the context of professional development at the PhD level.